Pemanfaatan Limbah Plastik Sebagai Bahan Penciptaan Patung Miniatur Rusa - M. Andri Bagustara Barus; Muslim Muslim (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
Sculpture is a field of three-dimensional fine art that has dimensions of height, width, and length. According to M. Susanto in his book Diksi Seni Rupa (2002) Miniature is a model, replica, prototype, and scale model as well as various forms of fine art made in small sizes. The author uses the Assembly Technique which in the manufacturing process uses a tool, namely Solder to melt Plastic Waste. Waste is a very important environmental problem, especially in urban areas to create this work, the author uses the Sp. Gustami creation method. The stages of the process of creating a work of art from this method include: 1.Exploration Stage 2. Improvisation/Experimentation Stage 3. Formation/Manifestation Stage. The results of the creation of this Deer miniature statue produced 12 three-dimensional sculptures of various sizes. The process of creating this sculpture began with determining the design, assembling the frame, wrapping plastic around the frame and then melting it, after that forming the details and footing of the statue so that the statue can stand. after that coloring using a spray car, the last step is to give clear to the statue